Bid outcome processing in Vickrey auctions: An ERP study. (16th June 2022) - Newton‐Fenner, Alice; Tyson‐Carr, John; Roberts, Hannah; Henderson, Jessica; Hewitt, Danielle; Byrne, Adam; Fallon, Nicolas; Gu, Yiquan; Gorelkina, Olga; Xie, Yuxin; Pantelous, Athanasios; Giesbrecht, Timo; et al.
Abstract: Online retailers often sell products using a socially competitive second‐price sealed‐bid auction known as a Vickrey auction (VA), an incentivized demand‐revealing mechanism used to elicit players' subjective values. The VA presents a situation of risky decision‐making, which typically implements value processing and a loss aversion mechanism. Neural outcome processing of VA bids are not known; this study explores this for the first time using EEG. Twenty‐eight healthy participants bid on household items against an anonymous, computerized opponent. Bid outcome event‐related potentials were predicted to differentiate between three conditions: outbid (no‐win), large margin win (bargain), and small margin win (snatch). Individual loss aversion values were evaluated in a separate behavioral experiment offering gains or losses of variable amounts but equal chances against an assured gain. Processing outcomes of VA bids were associated with a feedback‐related negativity (FRN) potential with a spatial maximum at the vertex (251–271 ms), where bargain win trials resulted in greater FRN amplitudes than snatch win trials. Additionally, a P300 potential was sensitive to win versus no‐win outcomes and to retail price. Individual loss aversion level did not correlate with the strength of FRN or P300. Results show that outcome processing in a VA is associated with FRN that differentiates between relatively advantageous and less advantageous gains, and a P300 that distinguishes between the more and less expensive auction items. Our findings pave the way to an objective exploration of economic decision‐making and purchasing behavior involving a widely popular auction. Abstract : This study is the first to utilize a prominent online purchasing paradigm to provide insight into the neural mechanisms of economic decision‐making under risk. Feedback‐related potentials showed sensitivity to instantaneous evaluations of the relative value of gain outcomes, and encoded the magnitude of the auctions outcome rewards.